Parameter development for the MIG welding of high strength aerospace aluminium alloys - Thomas, A. W. (Cranfield University, 2000)
Both dip and pulsed modes of metal transfer were investigated to establish which method produced the better bead geometry and penetration on 2024 and 2014 aluminium alloys using 2319 filler wire. The MIG electrode configuration used was electrode positive, which provides cathodic cleaning for aluminium alloys. Some initial work was also carried out using 6013 with 2319 as the consumable. A second part of the project involved the investigation of different combinations of shielding gas, and during both this and the previous task it was necessary to adjust the welding parameters to achieve acceptable welds. Initially, visual inspection and measurement of bead geometry were used for analysing the welds, but macrographs/micrographs, radiographs, hardness profiles and tensile tests were carried out to look more closely at the welds, once acceptable bead geometry and penetration was obtained. The microstructure was investigated to ascertain the extent of any porosity and chemical changes that might affect the mechanical performance of the joint by depletion of alloying elements in the HAZ. Pulse mode metal transfer improved the weld properties in comparison with the use of dip mode and was therefore used for all the work following the first section. During the work relating to shielding gas composition it was found that a 30% helium balance argon shielding gas produced the best results. It was observed during the speed trials that porosity increased with speeds in the region of 1000mm/min and also below 650mm/min. Pulse frequency and pulse time seemed to affect the arc performance and also influenced the levels of porosity. The need to thoroughly clean the joint area was also seen to be paramount in reducing porosity to a minimum. Hardness profiles indicated a dip in hardness just inside the HZ adjacent to the fusion line, with all tensile specimens failing at this point when the beads were left on. The tensile results carried out on 1.6mm 2024 at Cranfield using 30% helium in the shielding gas produced UTS strengths equivalent to 85% compared to parent metal strength, while those performed by Shorts produced UTS results up to 89%. This indicates an increase in strength over previous published results of 100%. Ibbotson cites two sets of TIG welds having UTS values of 191 and 194 MPa equivalent to 42% compared to parent metal strength while the welds produced at Cranfield using 30% helium in the shielding gas were 402 l\/IPa, equivalent to 86%. The tensile results for the 2mm 2014 aluminium alloy were even better, producing UTS results equivalent to 94% compared to the parent metal. With the 2014 alloys Ibbotson cites two sets of welds in both TIG and MIG and here UTS results were 221 and 243 MPa, equivalent to 55% compared to parent metal i ABSTRACT MIG Welding Aluminium alloys strength, while similar welds produced at Cranfield were 395MPa equivalent to 94%. The fractographs for this showed the start of a shear fracture indicating that the strength was nearing that of the parent material. Against these results even the thick section ]2.7mm 7150 welds having a UTS of 347MPa equivalent to 58% compared to parent metal strength look quite promising. The time trials relating to the natural age hardening process on 2024 welds confirmed that they achieve their maximum strength after 30 days, increasing by some 15% from half an hour after welding to 30 days. The use of thick section materials in the form of 12mm 2024 and 12.7mm 7150 became a requirement during the latter stages of the project with the investigation into the use of a number of commercially available filler wires dominating the research. Post weld heat treatment was seen to improve the strength of the welded joints when employing several different filler wires, but when incorporating a dual post weld heat treatment with 7150 using 1.6 5180 filler wire a marked improvement was observed. Arc monitoring techniques were used in the form of Arcwatch to log the arc voltage and welding current values, and a number of statistical evaluations were conducted during the project using the Arcwatch data. Geometrical data relating to weld bead dimensions was collected at numerous stages throughout the research and employed to build a joint prediction statistical model. This provides the end user with a means of process parameter selection and a visualisation of the influence of parameter variation on weld bead geometry. It has clearly been demonstrated that it is possible to produce viable welds using the MIG welding process with electrode positive, with comparatively low heat inputs when using a number of different high strength aluminium alloys and different composition filler W1I`CS. This piece of research has involved the welding of high strength aluminium alloys that have, in the past been classified as difficult to weld and with the 7xxx series, regarded unweldable. The results illustrate a major advancement in the welding of high. strength aluminium alloys, represent a considerable improvement in the strengths obtained in weldments using these alloys and has encouraged the U aerospace industry to pursue further research in this field.